A descriptive study on mercury handling, waste collections and disposal practices of the dental staff in San Pedro, Laguna - Mumpar, Ma. Adelcy H.; Magtanong, Danilo L. (Adviser).
Mercury toxicity has been one of the leading concerns among dentists and patients that seriously affected the popularity of one of the most significant dental materials ever to be developed, which is dental amalgam. After many researches conducted, they came out with the recommendations on proper mercury hygiene to address this issue. The primary aim of the study was to know whether the dentists practicing in San Pedro, Laguna are practicing the proper way of handling, collecting, and disposing mercury waste as recommended by the FDI and ADA. A descriptive research method was used to study the practices of 35 dentists, who were asked to answer a survey questionnaire. In the results, the handling techniques of the respondents are in favor with the recommended handling techniques by the FDI and the ADA in many aspects. It was noticed, though, that the collection and disposal practices regarding mercury wastes do not agree to the ones recommended by the FDI and ADA. Therefore, the following conclusions were derived: that most of the respondents practice the proper mercury handling techniques as recommended by the FDI and the ADA; and that most of the respondents do not practice the proper collection and disposal of excess mercury and amalgam scraps, as well as the proper management of mercury spills, as suggested by the FDI and the ADA, in their respective clinics.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Hazardous wastes -- Management